Hubungan Pengetahuan Gizi dan Aktivitas Fisik dengan Status Gizi Remaja Perempuan di SMP Negeri 1 Banjarbaru - Sarah Ariaini; Ainun Nisa; Yulianti Yulianti; Siti Aisyah Solechah (HB PRESS, 2022)
Nutritional status is a determining factor for adolescent quality because a person in adulthood is determined by nutritional status in adolescence. The process of growth and development will be perfect with optimal nutritional status. The purpose of this study was to determine the relationship between nutritional knowledge and physical activity with the nutritional status of adolescent girls in the 8th grade of State Junior High School 1, Banjarbaru. This study used an analytical method with a cross-sectional design. The population in this study was 119 students in the 8th grade of Junior High School 1, Banjarbaru. The research instruments used were questionnaires, a stature meter, and a digital weight scale. The data were analyzed using the chi-square test. The results showed that most of the respondents (77.3%) had good knowledge, 54.6% had moderate physical activity, 53.8% had good nutritional status. The statistical tests showed a significant relationship between nutritional knowledge and the nutritional status of adolescent girls in Junior High School 1, Banjarbaru (p=0.000) and physical activity had a relationship with the nutritional status of adolescent girls in Junior High School 1, Banjarbaru (p=0.000). Based on this study, it can be concluded that nutrition knowledge and physical activity are associated with the nutritional status of adolescent girls. Therefore, respondents are expected to maintain their nutritional status by regularly monitoring their weight and height.